Deconstruction of Social Views towards Women in the Biographic of Jejak Sang Pencerah Novel by Didik L Hariri and His Integration in Research Course and Appreciation of Pfiction Prose - Abdul Hafid; Ismail Marzuki; Aca Fatima Waripang; Isni Irna Jaya (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aimed to explain the deconstruction of social views of women in the novel Biography of Jejak Sang Pencerah by Didik L Hariri. In this study was explained about the author’s the integration of research results in the subject of study and appreciation of prose fiction. The approach used in this study was qualitative, the type of research is literature study, primary data: the novel Biography of Jejak Sang Pencerah by Didik L Hariri, secondary data: books, and journals. Data collection techniques of this study used library techniques. The data analysis technique used the Miles and Hubermen interactive model. Based on the results of data analysis, there were severals deconstructions of social views of women in the first novel Biography of Jejak Sang Pencerah by Didik L Hariri, the deconstruction of social views that considered women to be identical with housewives and uneducated. Secondly, the deconstruction of the social view that men are prioritized to get an education. Thirdly, the deconstruction of the idea that women cannot be respected figures. Fourth, deconstruct the culture that giving birth to the first child with a female gender is a disgrace. Sixth, the deconstruction of the social view that woman cannot organized. Seventh, the cultural deconstruction of a patriarchal society is described with noble tasks. Eighth, deconstruction of social views which is also shown by diplomacy carried out by women. The results of this study can be integrated into courses, especially the subject of the Study and Appreciation of Fiction Prose.